Do monetary indicators lead euro area inflation? - Boris Hofmann (European Central Bank (ECB), 2008)
This paper assesses the performance of monetary indicators as well as of a large range of economic and financial indicators in predicting euro area HICP inflation out-of-sample over the period first quarter 1999 till third quarter 2006 considering standard bivariate forecasting models, factor models, simple combination forecasts as well as trivariate two-pillar Phillips Curve forecasting models using both ex-post revised and real-time data. The results suggest that the predictive ability of money-based forecasts relative to a simple random walk benchmark model was high at medium-term forecasting horizons in the early years of EMU, but has substantially deteriorated recently. A significantly improved forecasting performance vis-à-vis the random walk can, however, be achieved based on the ECB's internal M3 series corrected for the effects of portfolio shifts and by combining monetary and economic indicators.
Keywords: E31; E40; C32; 330; euro area; inflation; leading indicators; Money; Inflation; Prognoseverfahren; Monetärer Indikator; Geldmenge; Eurozone; EU-Staaten